The First Harmonic of Radial Pulse as an Early Predictor of Silent Coronary Artery Disease and Adverse Cardiac Events in Type 2 Diabetic Patients - Chi-Wei Chang; Kuo-meng Liao; Yi-Ting Chang; Sheng-Hung Wang; Ying-chun Chen; Gin-Chung Wang (Cardiology Research and Practice)
Background. It has been reported that harmonics of radial pulse is related to coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM). It is still unclear whether or not the first harmonics of the radial pulse spectrum is an early independent predictor of silent coronary artery disease (SCAD) and adverse cardiac events (ACE). Objectives. To measure the risk of SCAD in patients with T2DM and also to survey whether or not an increment of the first harmonic (C1) of the radial pulse increases ACE. Methods. 1968 asymptomatic individuals with T2DM underwent radial pulse wave measurement. First harmonic of the radial pressure wave, C1, was calculated. Next, the new occurrence of ACE and the new symptoms and signs of coronary artery disease were recorded. The follow-up period lasted for 14.7 ± 3.5 months. Results. Out of 1968 asymptomatic individuals with T2DM, ACE was detected in 239 (12%) of them during the follow-up period. The logrank test demonstrated that the cumulative incidence of ACE in patients with C1 above 0.96 was greater than that in those patients with C1 below 0.89 (P<0.01). By comparing the data of patients with C1 smaller than the first quartile and the patients with C1 greater than the third quartile, the hazard ratios were listed as follows: ACE (hazard ratio, 2.29; 95% CI, 1.55–3.37), heart failure (hazard ratio, 2.22; 95% CI, 1.21–4.09), myocardial infarction (hazard ratio, 2.44; 95% CI, 1.51–3.93), left ventricular dysfunction (Hazard ratio, 2.01; 95% CI, 0.86–4.70), and new symptoms and signs for coronary artery disease (hazard ratio, 2.03; 95% CI, 1.45–2.84). As C1 increased, the risk for composite ACE (P<0.001 for trend) and for coronary disease (P<0.001 for trend) also increased. The hazard ratio and trend for cardiovascular-cause mortality were not significant. Conclusions. This study showed that C1 of the radial pulse wave is correlated with cardiovascular events. Survival analysis showed that C1 value is an independent predictor of ACE and SCAD in asymptomatic patients with T2DM. Thus, screening for the first harmonic of the radial pulse may improve the risk stratification of cardiac events and SCAD in asymptomatic patients although they had no history of coronary artery disease or angina-related symptom.